Method for improving joint strength of graphite and electromagnetic pure iron
The microstructure is formed through laser processing and soldered in a vacuum furnace, which solves the problems of presintering complexity and poor fillability of brazing materials in the connection between ceramic composites and electromagnetic pure iron, significantly improves the strength and stability of the joints, and is suitable for Thrust application in high temperature environment.
Patent Information
- Application Number
- CN202411420646.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has problems such as complex presintering process, poor fillingability of liquid-phase brazing alloys, and unstable joint strength in the structural design of ceramic composite materials and electromagnetic pure iron connection joints, especially in high temperature environments, resulting in a degradation of the performance of the thrust.
Laser processing equipment is used to form microstructures on the graphite surface, compressed air blow away floating dust, ultrasonic cleaning of brazing foils, and brazing is carried out in a vacuum furnace to build a blind hole or serrated gradient transition structure to improve joint strength.
The macroscopic groove presintering process is omitted, the fillability and strength stability of the brazed joint are improved, the thermal shock resistance of the graphite and electromagnetic pure iron are enhanced, and the shear strength is significantly improved.
Smart Images

Figure CN119282360A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic-electromagnetic pure iron dissimilar material connection, and specifically relates to a method for improving the strength of a graphite and electromagnetic pure iron joint by laser processing of surface microstructure. Background Art
[0002] With the gradual improvement of spacecraft's requirements for load ratio, velocity increment and attitude control accuracy, as well as the emergence of new space mission requirements, the demand for high-performance space power is becoming increasingly urgent. As the most mature electric propulsion device currently used in the world, Hall thrusters have the advantages of simple structure, high efficiency, high specific impulse, and high thrust density, and are suitable for on-orbit missions with high control accuracy requirements.
[0003] The outer magnetic pole of the inner magnetic core of the magnetic focusing Hall thruster is generally made of magnetic material DT4C. It faces ion bombardment in actual operation. The pollutants produced by ion sputtering of the plasma to the outer magnetic pole are continuously deposited on the inner wall of the discharge channel, greatly reducing the discharge efficiency of the thruster and causing the thruster performance to decline.
[0004] Graphite material has excellent thermal stability and ion sputtering resistance, especially ion sputtering resistance, which is at least one order of magnitude higher than that of general metal materials. Therefore, in order to avoid ion sputtering of the outer magnetic pole metal end surface by plasma, the design uses graphite material to cover the outer magnetic pole metal end surface.
[0005] At present, metal screws and nuts are mostly used to mechanically connect the metal end face of the outer magnetic pole and graphite, and then a graphite cap is covered on the surface of the metal nut to avoid ion sputtering of the metal nut. The structure is complex and the risk of the graphite cap falling off is very high. At the same time, graphite materials belong to powder metallurgy. Excessive tightening force of the screws will wear the graphite and produce excess powder; if the tightening force is too small, the threaded connection will loosen and easily fall off. Therefore, welding is an ideal solution to achieve the connection between the metal end face of the outer magnetic pole and graphite. At the same time, when the Hall thruster is actually working, the heat from the wall of the discharge channel will be transferred to the coil. In addition, the coil's own heating causes the coil to work in a higher temperature environment. If welding is used to connect the metal end of the coil with graphite, the heat dissipation problem of the coil can also be effectively solved.
[0006] There are few studies on the structural design and process of large-size ceramic composites and electromagnetic pure iron welding at home and abroad. In terms of the structural design of ceramic composite and electromagnetic pure iron joints, a paper entitled "A method for SiO 2f Chinese patent application ZL201010266686.0 entitled "Process for brazing of SiO2 composite ceramics with metal materials" proposes a method for brazing SiO2 composite ceramics with metal materials by mechanical processing. 2fA groove is made on the surface of the SiO2 ceramic composite to be welded, and then AgCuTi solder is filled in the groove. The mechanical processing method in this patent is a traditional milling method, and the groove depth is 0.6mm to 5.0mm. In order to make the groove full of solder, it must be pre-sintered, that is, the solder metal is first filled in the groove of the ceramic to be welded, and then the pre-sintered ceramic to be welded is formed after vacuum heating and cooling; then the solder is added between the pre-sintered ceramic to be welded and the metal to be welded, and brazing is performed in a vacuum furnace to form a joint. However, this method requires a pre-sintering process, and the groove size is large, the local stress is large, and in addition, the filling and uniformity of the liquid phase solder alloy in the larger size groove are worse, which is not conducive to the stability of the joint strength. Summary of the invention
[0007] In view of the above-mentioned situation of the prior art, the purpose of the present invention is to provide a structural design idea for the joint of heterogeneous brazing of graphite and electromagnetic pure iron, and to form a microstructure on the graphite surface by laser processing equipment. The size and depth of the microstructure are small. Compared with the mechanical macro grooves, the process of filling the macro grooves with powder solder for pre-sintering can be omitted. At the same time, the filling and uniformity of the liquid phase solder alloy in the microstructure are significantly better than those in the macro grooves, which can greatly improve the stability of the strength of the brazed joint.
[0008] The above object of the present invention is achieved through the following technical solutions:
[0009] A method for improving the strength of a graphite and electromagnetic pure iron joint, characterized in that the method is achieved by the following steps: ① using laser processing equipment to process a microstructure on a graphite welding surface, preferably a blind hole structure, but it can also be other microstructures, such as processing a strip groove on the graphite surface, and constructing a rectangular wave transition structure at the connection interface, wherein the graphite is preferably isostatic high-strength graphite; ② using compressed air to blow away floating dust on the graphite surface, and then wiping it with a dust-free cloth; ③ placing the electromagnetic pure iron material and the brazing foil in acetone for ultrasonic cleaning for 3min to 5min, and then drying it; ④ placing the brazing foil between the graphite processing surface and the electromagnetic pure iron, and fixing it with an elastic clip; ⑤ placing the assembled parts in a vacuum furnace for heating and brazing, the brazing temperature is 730℃ to 750℃, the insulation time is 5min to 15min, and after the insulation is completed, the temperature is controlled to cool to 400℃ at a cooling rate not higher than 4℃ / min, and then cooled to room temperature with the furnace before being taken out of the furnace.
[0010] Preferably, the blind hole has a hole diameter of 0.03-0.3 mm, a hole spacing of 0.03-0.3 mm, and a hole depth of 0.1 mm-0.5 mm.
[0011] Preferably, the solder is AgCuTi solder or AgCuInTi solder, with a thickness of 30-100 μm. The AgCuTi solder is obtained by adding Ti to AgCu eutectic, wherein the mass percentage of Cu is 26.6%-27.0%, and the mass percentage of Ti is 3.5%-5.0%; the mass percentage of Cu in the AgCuInTi solder is 28%-30%, the mass percentage of In is 13%-15%, and the mass percentage of Ti is 2%-3%.
[0012] The present invention utilizes laser processing equipment to process blind hole structures with different hole diameters and hole spacings on the graphite surface to be welded. During the brazing process, the brazing material is melted and filled into the blind hole and between the graphite / electromagnetic pure iron, and a serrated gradient transition structure is constructed between the connection interface of the graphite and the electromagnetic pure iron, thereby alleviating the residual stress of the joint. At the same time, the brazing material metal in the blind hole can play a mechanical pinning role to improve the strength of the joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a schematic diagram of a graphite and electromagnetic pure iron joint after surface microstructure processing by laser according to the present invention.
[0014] Figure 2 This is a SEM image of the graphite and electromagnetic pure iron joint after the surface microstructure is processed by laser according to Example 1.
[0015] Figure 3 This is a SEM image of the graphite and electromagnetic pure iron joint after the surface microstructure is processed by laser according to Example 2. DETAILED DESCRIPTION
[0016] In order to more clearly understand the purpose, technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0017] The biggest difficulty in brazing ceramics and metals is the large difference in thermal expansion coefficients between the two. The residual stress after welding is too large, which seriously weakens the strength of the joint. When subjected to alternating hot and cold shocks, the ceramic / metal heterogeneous joint quickly fails and cracks due to the accumulation of residual stress. Although the method of machining macro grooves can relieve residual stress and improve the joint's resistance to thermal shock, due to the poor filling of macro groove brazing material, some grooves will lack material and form voids, resulting in unstable joint strength, large dispersion, and low joint reliability.
[0018] To this end, the present invention proposes a method for improving the strength of a graphite and electromagnetic pure iron joint by laser processing a surface microstructure, which is characterized by being achieved by the following steps: ① processing a blind hole structure on a graphite welding surface using a laser processing device; ② using compressed air to blow away floating dust on the graphite surface, and then wiping it with a dust-free cloth; ③ placing the electromagnetic pure iron material and the active brazing sheet in acetone for ultrasonic cleaning for 3min to 5min, and then drying; ④ placing a brazing sheet between the graphite processing surface and the electromagnetic pure iron, and fixing it with an elastic clip; ⑤ placing the assembled parts in a vacuum furnace for heating and brazing, the brazing temperature is 730℃ to 750℃, the insulation time is 5min to 15min, and the vacuum degree of the vacuum brazing furnace should be lower than 5×10 -3 Pa, after the insulation is completed, the steel is cooled to 400°C at a cooling rate not higher than 4°C / min, and then cooled to room temperature with the furnace before being taken out of the furnace.
[0019] Figure 1 The figure schematically shows a graphite and electromagnetic pure iron joint after laser processing of the surface microstructure according to the present invention. As shown in the figure, a brazing foil is placed between the graphite 1 and the electromagnetic pure iron 3. During the brazing process, the brazing material melts and fills the microstructure, and forms a serrated brazing metal 2 after solidification, so that the connection interface is transformed from the original straight interface to a wavy interface, and a metal / ceramic gradient transition structure is formed near the connection interface between the graphite and the electromagnetic pure iron to achieve a connection function combining mechanical bite and chemical bond.
[0020] In the following examples, the model of the laser precision processing equipment is MD100B, the graphite is isostatic high-strength graphite, and the size is 3×4×10 mm. 3 , the laser processing surface is 3×10mm 2 The laser power was set to 6 W, the scanning speed to 3000 mm / s, the defocus to 0 mm, and the number of scans to 1.
[0021] Embodiment 1:
[0022] 1. Process blind holes on the graphite surface to be welded, with a hole diameter of 0.2mm, a hole depth of 0.2mm, and a hole spacing of 0.2mm;
[0023] 2. Use compressed air to blow away the dust on the graphite surface, and then wipe it with a dust-free cloth;
[0024] 3. The solder is Ag-26.7Cu-4.5Ti (brand name Ticusi), 50μm thick, cut into 3.5×10.5mm with scissors 2 Solder sheet;
[0025] 4. Place the electromagnetic pure iron and solder sheet in acetone for ultrasonic cleaning for 5 minutes, take them out and dry them naturally;
[0026] 5. Place the Ag-26.7Cu-4.5Ti solder sheet between the graphite and the electromagnetic pure iron surface to be welded, fix it with ethyl α-cyanoacrylate as a binder, and then clamp it with a "C"-shaped elastic molybdenum clamp;
[0027] 6. Place the assembled parts in a vacuum furnace for heating and brazing. The brazing temperature is 750°C and the holding time is 10 minutes. After the holding period, cool them to 400°C at a cooling rate of 4°C / min, and then cool them to room temperature before taking them out of the furnace.
[0028] The obtained joint shear strength at room temperature is 15.95 MPa.
[0029] Joint organization Figure 2 shown.
[0030] Embodiment 2:
[0031] 1. Process blind holes on the graphite surface to be welded, with a hole diameter of 0.05mm, a hole depth of 0.2mm, and a hole spacing of 0.05mm;
[0032] 2. Use compressed air to blow away the dust on the graphite surface, and then wipe it with a dust-free cloth;
[0033] 3. The solder is Ag-26.7Cu-4.5Ti (brand name Ticusi), 50μm thick, cut into 3.5×10.5mm with scissors 2 Solder sheet;
[0034] 4. Place the electromagnetic pure iron and solder sheet in acetone for ultrasonic cleaning for 5 minutes, take them out and dry them naturally;
[0035] 5. Place the Ag-26.7Cu-4.5Ti solder sheet between the graphite and the electromagnetic pure iron surface to be welded, fix it with ethyl α-cyanoacrylate as a binder, and then fix it with an elastic molybdenum clamp;
[0036] 6. Place the assembled parts in a vacuum furnace for heating and brazing. The brazing temperature is 750°C and the holding time is 10 minutes. After the holding period, cool them to 400°C at a cooling rate of 4°C / min, and then cool them to room temperature before taking them out of the furnace.
[0037] The obtained joint shear strength at room temperature is 26.9 MPa.
[0038] Joint organization Figure 3 shown.
[0039] Embodiment 3:
[0040] 1. Process blind holes on the graphite surface to be welded, with a hole diameter of 0.2mm, a hole depth of 0.2mm, and a hole spacing of 0.2mm;
[0041] 2. Use compressed air to blow away the dust on the graphite surface, and then wipe it with a dust-free cloth;
[0042] 3. The solder is Ag-(28~30)Cu-14In-2.5Ti, 50μm thick, cut into 3.5×10.5mm with scissors 2 Solder sheet;
[0043] 4. Place the electromagnetic pure iron and solder sheet in acetone for ultrasonic cleaning for 5 minutes, take them out and dry them naturally;
[0044] 5. Place the Ag-(28~30)Cu-14I n-2.5Ti brazing filler metal sheet between the graphite and the electromagnetic pure iron surface to be welded, fix it with ethyl α-cyanoacrylate as a binder, and then fix it with an elastic molybdenum clamp;
[0045] 6. Place the assembled parts in a vacuum furnace for heating and brazing. The brazing temperature is 730°C and the holding time is 10 minutes. After the holding period, cool to 400°C at a cooling rate of 4°C / min, and then cool to room temperature before taking out of the furnace.
[0046] The obtained joint shear strength at room temperature is 16.7 MPa.
[0047] Embodiment 4:
[0048] 1. Process blind holes on the graphite surface to be welded, with a hole diameter of 0.05mm, a hole depth of 0.2mm, and a hole spacing of 0.05mm;
[0049] 2. Use compressed air to blow away the dust on the graphite surface, and then wipe it with a dust-free cloth;
[0050] 3. The solder is Ag-(28~30)Cu-14I n-2.5, 50μm thick, cut into 3.5×10.5mm with scissors 2 Solder sheet;
[0051] 4. Place the electromagnetic pure iron and solder sheet in acetone for ultrasonic cleaning for 5 minutes, take them out and dry them naturally;
[0052] 5. Place the Ag-(28~30)Cu-14I n-2.5 brazing material sheet between the graphite and the electromagnetic pure iron surface to be welded, fix it with ethyl α-cyanoacrylate as a binder, and then fix it with an elastic molybdenum clamp;
[0053] 6. Place the assembled parts in a vacuum furnace for heating and brazing. The brazing temperature is 730°C and the holding time is 10 minutes. After the holding period, cool to 400°C at a cooling rate of 4°C / min, and then cool to room temperature before taking out of the furnace.
[0054] The obtained joint shear strength at room temperature is 31.5 MPa.
[0055] Embodiment 5:
[0056] 1. Process blind holes on the graphite surface to be welded, with a hole diameter of 0.1mm, a hole depth of 0.2mm, and a hole spacing of 0.1mm;
[0057] 2. Use compressed air to blow away the dust on the graphite surface, and then wipe it with a dust-free cloth;
[0058] 3. The solder is Ag-26.7Cu-4.5Ti (brand Ticus I), 50 μm thick, cut into 3.5×10.5 mm with scissors 2 Solder sheet;
[0059] 4. Place the electromagnetic pure iron and solder sheet in acetone for ultrasonic cleaning for 5 minutes, take them out and dry them naturally;
[0060] 5. Place the Ag-26.7Cu-4.5Ti solder sheet between the graphite and the electromagnetic pure iron surface to be welded, fix it with ethyl α-cyanoacrylate as a binder, and then fix it with an elastic molybdenum clamp;
[0061] 6. Place the assembled parts in a vacuum furnace for heating and brazing. The brazing temperature is 750°C and the holding time is 10 minutes. After the holding period, cool them to 400°C at a cooling rate of 4°C / min, and then cool them to room temperature before taking them out of the furnace.
[0062] The obtained joint shear strength at room temperature is 20.77 MPa.
[0063] Embodiment 6:
[0064] 1. Process blind holes on the graphite surface to be welded, with a hole diameter of 0.1mm, a hole depth of 0.2mm, and a hole spacing of 0.1mm;
[0065] 2. Use compressed air to blow away the dust on the graphite surface, and then wipe it with a dust-free cloth;
[0066] 3. The solder is Ag-26.7Cu-4.5Ti (brand Ticus I), 50 μm thick, cut into 3.5×10.5 mm with scissors 2 Solder sheet;
[0067] 4. Place the electromagnetic pure iron and solder sheet in acetone for ultrasonic cleaning for 5 minutes, take them out and dry them naturally;
[0068] 5. Place the Ag-26.7Cu-4.5Ti solder sheet between the graphite and the electromagnetic pure iron surface to be welded, fix it with ethyl α-cyanoacrylate as a binder, and then fix it with an elastic molybdenum clamp;
[0069] 6. Place the assembled parts in a vacuum furnace for heating and brazing. The brazing temperature is 750°C and the holding time is 10 minutes. After the holding period, cool them to 400°C at a cooling rate of 4°C / min, and then cool them to room temperature before taking them out of the furnace.
[0070] The obtained joint shear strength at room temperature is 26.9 MPa.
[0071] The present invention utilizes laser processing equipment to process microstructures on the graphite surface to be welded. The specific advantages are as follows:
[0072] (1) During laser processing, the dust is blown away by air, and no coolant is required. Avoid the coolant from penetrating into the graphite and affecting its physical and chemical properties;
[0073] (2) The size and depth of the microstructure are small. Compared with the mechanical macro groove, the process of pre-sintering the macro groove by filling the powder solder can be omitted. Only a single layer of foil solder can be used, which can completely fill the microstructure after melting.
[0074] (3) The filling property of liquid solder alloy in microstructure is significantly better than that in macro grooves, which can avoid the formation of holes due to lack of material in the grooves. The strength of the brazed joint is increased and a high strength stability is maintained.
[0075] (4) A serrated gradient transition structure was constructed at the interface between graphite and electromagnetic pure iron, transforming the original straight interface into a wavy interface, achieving a connection function combining mechanical bite and chemical bond. Compared with the macro groove, the shear strength of the heterogeneous joint between graphite and electromagnetic pure iron obtained by laser processing of the surface microstructure was increased from 10.65MPa to 26.4MPa.
Claims
1. A method for improving the strength of graphite and electromagnetic pure iron joints, characterized in that The following steps are involved: ①Use laser processing to process microstructure on the graphite welding surface; ② Place the brazing foil between the graphite welding surface and the electromagnetic pure iron and fix it; ③ Heat and braze the assembled parts at a temperature of 730°C to 750°C and a holding time of 5min to 15min.
2. The method according to claim 1, wherein the microstructure machined on the graphite welding surface is a blind hole.
3. The method according to claim 2, wherein the blind hole has a hole diameter of 0.03-0.3 mm, a hole spacing of 0.03-0.3 mm, and a hole depth of 0.1 mm-0.5 mm.
4. The method according to claim 1, wherein when the graphite welding surface is 3×10 mm 2 The laser power was set to 6 W, the scanning speed to 3000 mm / s, the defocus to 0 mm, and the number of scans to 1.
5. The method according to claim 1, wherein in the hot brazing, after the heat preservation is completed, the temperature is controlled to cool to 400°C at a cooling rate not higher than 4°C / min, and then the furnace is cooled to room temperature before being taken out of the furnace.
6. The method according to claim 1, wherein the solder is AgCuTi solder or AgCuInTi solder, and has a thickness of 30 to 100 μm.
7. The method according to claim 6, wherein the mass percentage of Cu in the AgCuTi solder is 26.6% to 27.0%, and the mass percentage of Ti is 3.5% to 5.0%; the mass percentage of Cu in the AgCuInTi solder is 28% to 30%, the mass percentage of In is 13% to 15%, and the mass percentage of Ti is 2% to 3%.
8. The method according to claim 1, wherein the fixing comprises bonding and fixing the solder sheet to the graphite and electromagnetic pure iron surfaces to be welded using ethyl α-cyanoacrylate, and then clamping and fixing them using a "C"-shaped elastic molybdenum clamp.
9. The method according to claim 1, wherein the graphite is isostatically pressed high-strength graphite.
Citation Information
Patent Citations
Process for soldering SiO2f / SiO2 composite ceramic and metal material
CN101935226B
Laser surface pretreatment method for improving interface bonding strength
CN109702346A
Strip-shaped silver-copper-titanium active brazing filler metal and preparation method thereof
CN114921680A
Brazing process of IPG graphite-electromagnetic pure iron heterogeneous joint
CN117381092A